Biogasoline production from linoleic acid via catalytic cracking over nickel and copper-doped ZSM-5 catalysts - Gurdeep Singh, H.K. (Academic Press Inc., 2020)
Catalytic cracking of vegetable oil mainly processed over zeolites, and among all the zeolites particularly HZMS-5 has been investigated on wide range for renewable and clean gasoline production from various plant oils. Despite the fact that HZSM-5 offers a higher conversion degree and boost aromatics yield, the isomerate yield reduces due to high cracking activity and shape selectivity of HZSM-5. Hence, to overcome these problems, in this study the transition metals, such as nickel and copper doped over HZSM-5 were tested for its efficiencies to improve the isoparaffin compounds. The catalysts were screened with linoleic acid in a catalytic cracking reaction conducted at 450 áµC for 90 min in an atmospheric condition in batch reactor. Then, the gasoline composition of the organic liquid product (OLP) was analysed in terms of paraffin, isoparaffin, olefin, naphthenes and aromatics (PIONA). The results showed that Cu/ZSM-5 produced the highest liquid yield of 79.1, at the same time reduced the production of gas and coke to 18.8 and 0.7. Furthermore, the desired isoparaffin composition in biogasoline increased from 1.6 to 6.8 and at the same time reduced the oxygenated and aromatic compounds to 15.4 and 59.7, respectively. The linoleic acid as model compound of rubber seed oil, in the catalytic cracking reaction provides a clearer understanding of the process. Besides, the water gas shift (WGS) reaction in catalytic cracking reaction provides insitu hydrogen production to saturate the branched olefin into the desired isoparaffin and the aromatics into naphthenes. Â© 2020 Elsevier Inc.